Anatomical study of the so‐called "retromolar gland": Distinguishing normal anatomy from oral cavity pathology. Issue 4 (22nd February 2018) - Iwanaga, Joe; Nakamura, Ken; Alonso, Fernando; Kirkpatrick, Christie; Oskouian, Rod J.; Watanabe, Koichi; Tubbs, R. Shane
Abstract : The minor salivary glands in the retromolar trigone have rarely been studied. The aim of this study was to better define the anatomy of the minor salivary glands in the retromolar trigone and establish the relationships between these and adjacent structures. The gland in the retromolar trigone was exposed and its relationships to surrounding structures were observed on 20 cadaveric sides. The boundaries of the gland included the superior pharyngeal constrictor muscle, the tendon of the buccinator muscle, and loose connective tissue. The gland was not continuous with the pterygomandibular or parapharyngeal spaces, but loose connective tissue was present between glands in the retromolar trigone and the medial pterygoid muscle. To our knowledge, this is the first study to describe the detailed anatomy of the minor salivary gland in the retromolar trigone. We suggest that the minor salivary gland in the retromolar trigone should be named the "retromolar gland." Clin. Anat. 31:462–465, 2018. © 2018 Wiley Periodicals, Inc.